If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(m + 4) = 39 Reorder the terms: 3(4 + m) = 39 (4 * 3 + m * 3) = 39 (12 + 3m) = 39 Solving 12 + 3m = 39 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 3m = 39 + -12 Combine like terms: 12 + -12 = 0 0 + 3m = 39 + -12 3m = 39 + -12 Combine like terms: 39 + -12 = 27 3m = 27 Divide each side by '3'. m = 9 Simplifying m = 9
| 12+36x+27x^2=0 | | x-2x-25=0 | | t^4-7t^2-18=0 | | X=8+9Y-5*2 | | x=x+6 | | 60[100s]= | | 10x^2+21x-27=0 | | 28+x=24 | | 12d-6+4d= | | N+17=22 | | (y-2)-(Y+6)=4Y | | 19-A=3 | | 21=7S | | -380+x+x^2=0 | | 99-M=3 | | 7x-4-5x+2=10x+6-7x-4 | | a^2-18ab-40b^2= | | 2x^2-3x=35 | | 3(t-1)=qt | | -15=5b+12-2b | | 8a+20b=100 | | 99-M=72 | | a^2+17ab+72b^2= | | a^2+4ab-21b^2= | | 9n+45=10n-120 | | m^2+15m-100= | | m^2-15m-100= | | 3-46=10b+10 | | -33+4x=x | | m^2+25m+100= | | (8x+10y-4)-(4x+3y-6)= | | 7x+20=160 |